1997
DOI: 10.1037/0882-7974.12.4.667
|View full text |Cite
|
Sign up to set email alerts
|

Continued inhibitory capacity throughout adulthood: Conceptual negative priming in younger and older adults.

Abstract: Two negative priming experiments in older and younger adults are reported. Participants in Experiment 1, involving both positive and negative priming conditions, showed both types of priming. There were no significant differences between age groups. If anything, older participants showed more negative priming. In Experiment 2, involving only negative priming conditions, similar results were obtained. Our findings rule out possible effects of experimental conditions that episodic retrieval theorists have sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
42
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 41 publications
11
42
1
1
Order By: Relevance
“…However, some studies have indicated that there is preserved identity negative priming in older adults that results from distractor suppression (Sullivan & Faust, 1993;Sullivan et al, 1995). Interestingly, identity negative priming has been found in older adults even in experiments designed to decrease the influence of memory retrieval-for example, by not including attended repetition trials (Gamboz, Russo, & Fox, 2000;Schooler et al, 1997). Negative priming in older adults appears to be different from the negative priming found in younger adults.…”
mentioning
confidence: 49%
“…However, some studies have indicated that there is preserved identity negative priming in older adults that results from distractor suppression (Sullivan & Faust, 1993;Sullivan et al, 1995). Interestingly, identity negative priming has been found in older adults even in experiments designed to decrease the influence of memory retrieval-for example, by not including attended repetition trials (Gamboz, Russo, & Fox, 2000;Schooler et al, 1997). Negative priming in older adults appears to be different from the negative priming found in younger adults.…”
mentioning
confidence: 49%
“…In particular, the findings are consistent with the previous result of intact control processes in young-old (though not old-old) adults' retrieval-induced forgetting and think/ no-think impairment (Asian & Bäum!, in press;Murray et al, 2011), and findings outside the memory domain reporting evidence for control processes that remain intact for the bigger part of the life span (e.g., Kieley & Hartley, 1997;Schooler et al, 1997). In a recent series of meta-analyses, Verhaeghen (2011) searched for a specific age-related deficit in (undifferentiated) older adults' executive functioning, employing tasks tapping local task-shifting costs, inhibition of retum, negative priming, and Stroop.…”
Section: Discussionmentioning
confidence: 98%
“…Since they failed to reveal differences in identity NP between young and older adults, May et al (1995) assumed that episodic retrieval accounts for NP in older adults in this study. When omitting a repeated-target condition, however, Schooler, Neumann, Caplan, and Roberts (1997) found significant NP of almost the 284 S. J. TROCHE ET AL. same extent in older and young adults. Therefore, application of a repeat condition does not appear to be necessary to produce identity NP in older adults.…”
Section: Introductionmentioning
confidence: 86%